Transitivity of English Verbs in Short Story “Pinnochio” - Sada Devi Pradnyadari, Putu Ayu (Humanis, 2018)
This undergraduate thesis examines the type of transitiv e verbs found in a children story entitled “Pinocchio”, which was taken from the children story book entitled Disney Storyland Treasury , and analyz es the degree of transitivity found in the story. The data were collected using the documentation method and were analyzed using the descriptive qualitative method. In addition, in order to present the data analysis clearly, both formal and informal methods were used since the data were described in form of sentences and tables. The main theory applied in this study is proposed by Hopper and Thom p son (1980) about transitivity, who said that transitivity is a matter of degree and partly because obviousness of change in the object. This theory is supported by the types of verb proposed by Givon (1984), which is used to find out the types of verb in the story. The finding of the analysis showed that there were three types of verb s found in the story namely state verb, action verb and process verb. Each verb has different degree of transitivity, where the degree of state verb is categorized as low in transitivity, action and process verb s ha ve the highest degree of parameter of transitivity.